Redefining the role of food aid - Hoddinott, John F.; Cohen, Marc J.; Bos, Maria Soledad (International Food Policy Research Institute, 2004)
The principal objective of food aid, besides responding to needs created by conflict, and other disasters, should be to provide an insurance function for those events for which existing insurance mechanisms function poorly